Managing Distress Over Time in Psychotherapy: Guiding the Client in and Through Intense Emotional Work - Muntigl, Peter (Frontiers in Psychology, 2020)
Clients who seek psychotherapeutic treatment have had personal experiences involving some form of distress. Although research has shown that the client’s ability to experience and express painful emotions during therapy can have therapeutic benefit, it has also been argued that displaying distress may convey a form of helplessness and vulnerability and, thus, clients may be reluctant to cast themselves in this light. Using the methods of conversation analysis, this paper explores how a client’s upsetting experience is managed over the course of a single session of client-centered therapy. The main analytic focus will be on 1) the different therapist practices used to orient to the client’s distress; 2) the varying forms of client opposition to the therapist’s attempts to work with the distress; and 3) the context sensitivity of orienting to distress and how certain practices may be uniquely shaped by what had occurred in prior talk. It was found that, whereas certain types of therapist responses tended to be endorsed by the client, others were forcefully rejected as inappropriate displays of understanding or empathy. By focusing on repeated sequential episodes over time in which a client conveys distress, followed by the therapist’s response, this paper sheds light on the interactional trajectory through which a client and therapist are able to resolve impasses to emotional exploration and to successfully secure extended and intense emotional work.